Mammals in the Collection of the National Museum of Natural History and Science (University of Lisbon, Portugal): A Contribution to Research and Conservation - Maria da Luz Mathias; Rita I. Monarca; Tomé Neves; Joaquim T. Tapisso; Maria Judite Alves; Maria da Graça Ramalhinho (Diversity)
Museum collections serve as valuable repositories of biodiversity, offering a substantial amount of data and specimens for scientific research. This study describes the intrinsic value of the mammal collection at the National Museum of Natural History and Science of the University of Lisbon (Portugal) (MUHNAC), and its nationwide representativeness, with the final aim of revealing its potential to support research and conservation initiatives. The collection includes 6158 specimens, from 131 species, across 10 orders, the great majority collected within Portugal, although a small dataset mostly from other parts of Europe and Africa is also available. The most represented orders are Rodentia, Eulipotyphla, and Carnivora, in contrast to Chiroptera, Cetacea, and Artiodactyla. Approximately 40% of the species within these groups are of conservation concern according to both national and international conventions, with nearly 20% at risk of extinction based on IUCN criteria. Additionally, the representativity of species in MUHNAC reflects the museum’s coverage of species records across the country, with smaller, non-threatened species being more prominently represented and larger, at-risk species being comparatively underrepresented. The influence of conservation, economic, legal, and ethical factors on the species spatial coverage is discussed, providing insights into the variability observed in museum collections.